2023
DOI: 10.3390/en16247927
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Use of Rational Electric Vehicle Battery Design as an Example of the Introduction of the Fit for 55 Package in the Real Estate Market

Oleksandr Beshta,
Dariusz Cichoń,
Oleksandr Beshta
et al.

Abstract: The European climate law contains a mandatory EU climate target of reducing emissions in the EU by at least 55% by 2030; to realistically implement it, a transformation of many economic sectors is required. The main solutions focus on energy production. However, an equally important aspect is its storage. It represents the biggest challenge to ensure the stability of energy use in the real estate market. Today, lithium-ion batteries are the most promising batteries. They have the advantages of high efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…They can be components of composite fuels that can improve the technological characteristics of production processes and contribute to obtaining a better product in terms of the above quality indicators. This waste is lignin, a residue of the chemical industry [22,23].…”
Section: The Choice Of Object To Studymentioning
confidence: 99%
“…They can be components of composite fuels that can improve the technological characteristics of production processes and contribute to obtaining a better product in terms of the above quality indicators. This waste is lignin, a residue of the chemical industry [22,23].…”
Section: The Choice Of Object To Studymentioning
confidence: 99%
“…Research on the development of the new indicator was based on drone flights using a DJI Phantom 4 drone equipped with a multispectral camera. The new GRWI index is based on the formula of the GRNDVI (Green Red Normalized Difference Vegetation Index) [30], considering the rededge band (Equation 1). The index takes values from -1 to 1, where values for aquatic areas range from 0.2 to 0.6 [24].…”
Section: Grwi -Green Red Water Indexmentioning
confidence: 99%
“…By following these steps and implementing comprehensive noise control measures, mining enterprises can effectively safeguard their workers from the adverse effects of noise exposure while maintaining a safe and healthy work environment. While standard certified measuring instruments are conventionally used to gauge hazardous and harmful factors at work, recent research has demonstrated the feasibility of employing modern information and computer technologies [18,19].…”
Section: Introductionmentioning
confidence: 99%